ÁDEBIYAT SABAQLARĺNDA SHĺǴARMALARDĺ BLUM TAKSONOMIYASĺ TIYKARĺNDA OQĺTĺW - Mambetova, G. (SCIENCE and SOCIETY, 2021)
In this article, the ways of using Blum's taxonomy in teaching Karakalpak literature in schools are studied on the basis of T.Kayipbergenov's "Maman biy afsona".
Keywords: literature lesson; taxonomy; methodology; knowledge; understanding; use; analysis; synthesis; evaluation